Gemeente Kediri: Dinamika Kota Kediri Masa Hindia Belanda Hingga Penjajahan Jepang 1906-1945, oleh Saichurrohman dan Wiretno - Imam Basthomi (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2025)
This book by M. Saichrrohman and Wiretno has the original title in Indonesian, namely "Gemeente Kediri: Dinamika Kota Kediri Masa Hindia Belanda Hingga Penjajahan Jepang 1906-1945". The initial manuscript of this book originated from two separate thesis manuscripts written by both authors during their studies in the History Study Program at Airlangga University's Faculty of Cultural Sciences in Surabaya. The two manuscripts examine the city of Kediri with interrelated temporal boundaries, making it easy to publish this work as a cohesive book. This book is the first comprehensive work to discuss the history of the city of Kediri. This book can serve as a starting point for research on the history of the city of Kediri, covering other themes such as politics, economics, and culture.